Assessment of donkeys' welfare in Addis Ababa and Ambo, Ethiopia - Björkengren, Julia (2016)
In Ethiopia, working donkeys provide an essential transport resource and the people in the poor communities are highly dependent on these animals. The donkeys are often owned by people who belong to the poorest section of society, which results in that the animals are forced to work hard without adequate resources as feed, water, veterinary treatment and appropriate loading equipment. Consequently, the working donkeys in Ethiopia suffer from multiple welfare problems. The main aim of this study was to perform an animal welfare assessment and analyse the prevalence of different health and behavioural problems of the working donkeys in the cities Addis Ababa and Ambo, Ethiopia. An animal welfare assessment protocol in line with Welfare Quality® was used to assess 84 pack donkeys. The donkeys living and working conditions were observed using a resource- and management-based protocol. Further, 22 donkey owners were interviewed regarding feeding, water and health care routines. The result showed that resources as water, feed and shade for the donkeys were lacking at markets and other work sites. Almost 30% of the working donkeys were apathetic and 23.8% were unresponsive. The majority of the donkeys were scored as thin with Body Condition Score (BCS) of 1 or as fair with BCS of 2. Bad coat and skin condition, lesions and eye abnormalities were the most prevalent health problems. Other welfare problems that had lower prevalence but probably caused pain for the donkeys were hoof problems, abnormal gait and back pain. In Ambo, it was common to treat sick and wounded donkeys with traditional remedies which could deteriorate the welfare of the donkeys. To improve the conditions for the working donkeys, it is important to enhance the knowledge of the owners and to improve the status for these animals.